Smart Spectrophotometric Method Development for Simultaneous Estimation of Antidiabetic Drugs in Formulations - Attimarad, Mahesh; Venugopala, Katharigatta Narayanaswamy; Shafi, Sheeba; Balgoname, Abdulmalek Ahmed; Altaysan, Abdulrahman Ibrahim (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: An anti-diabetic formulation consisting of vildagliptin and remogliflozin was prescribed for better glycemic control. In the present study a simple, rapid derivative spectrophotometric methods were evolved to analyze these two analytes from the formulations. Methods: Two processed UV spectrophotometric methods were established by measuring the peak amplitude at zero-crossing of second derivative spectra of analytes. The second procedure comprehends the generation of zero - order spectra from the mixture of analyte spectra by division and multiplication by the pure analyte spectra to remove the effect of one of the analytes. Results: Both methods showed linearity concentrations in the range of 2-75 μg/ml for RGF and 2-50 μg/ml for VGT. The low LOD and LOQ found for RGF and VGT by both methods indicated the good sensitivity of the methods. The mean percentage recovery was 98.60 % and 100.78%, for RGF and 98.81 % and 99.15 % for VGT, with low percent relative error. The % RSD for intra and inter-day precision was less than ±2%. Finally, the planned methods were employed for the assay of the VGT and RGF from the medicine and the outcomes were matched with the reported methods. Conclusion: The assay results of the formulation were in agreement with the concentration of labeled amount and no significant difference was observed in the results when compared to the reported method. Hence, the anticipated procedures could be applied for the routine quality control of formulations consisting of VGT and RGF.
Keywords: Antidiabetics; Vildagliptin; Remogliflozin; Derivative spectrophotometry; Formulation; Validation